Penerapan Metode Weighted Product Dalam Penentuan Penerimaan Bantuan Ternak Ayam - Sena Wijayanto; Monsya Juansen; Sandhy Fernandez; M Yoka Fathoni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
One of the problems experienced by many countries, especially developing countries and a concern is poverty. This matter must be immediately addressed by the government so that it is necessary to find a way out so that people's lives will be better. One of the solutions that the government has taken is to provide assistance, for example the assistance of chickens. However, the provision of assistance is still uneven, one of which is due to errors during the data assessment process for prospective beneficiaries. Therefore it is necessary to make a Decision Support System (DSS). DSS built web-based using the incremental model for system development. the method implemented in the DSS to determine the recipient of chicken livestock assistance is the weighted product. From the results of the study, it was found that the prospective recipient of chicken livestock assistance who had the greatest preference weight was obtained by Pornomo Sidi, which was 0.1390. In addition, the system created is very attractive and can display a list of potential recipients of chicken livestock assistance effectively and efficiently.